Eyes of the Society: How Malawian Journalists Utilise Question Time During Political Press Briefings. Issue 3 (2nd July 2020) - Sharra, Albert
ABSTRACT: Question time during political press briefings presents one of the few occasions for the press to exercise its watchdog role. However, the way the press utilises this opportunity varies. Drawing on journalistic interview concept, which treats interviews between journalists and politicians as an "encounter of two institutions", each making a claim on legitimacy, this qualitative study conducted a content analysis on 10 recorded political press briefings held between April 2019 and April 2020, a period dominated by many political press briefings on elections, to examine how Malawian journalists utilise question time during political press briefings. The analysis is complemented by interviews with 15 Malawian journalists. Findings show that although question time gives Malawian journalists an opportunity to exercise their watchdog role through asking questions, the occasion is in most cases abused by both parties in the interlocution. Furthermore, political interests, freebies and power disparity between press briefing organisers and journalists compromise the independence of the press and its watchdog role.